PENGEMBANGAN HUTAN ADAT TARUPRAMANA DI DESA BATUBULAN KECAMATAN SUKAWATI KABUPATEN GIANYAR - N.W. Suniti; W.P. Windia; N.L.R. Purnawan; I.A. Arthayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
Community service activities is aimed at the development of indigenous forest in order to preserve theenvironment of indigenous Balinese culture and appeal of ecological tourism through the creation ofnurseries, planting and plant arrangement taru pramana in Batubulan Sukawati Gianyar Regency. Themethod applied in community empowerment activities IbW (science and technology for the Region) is asfollows: (1) Coordination and communication are participatory with farmers' groups to create a program fromthe planning, operational and evaluation; (2) Guidance for the perception and understanding of theinnovations or programs implemented; (3) training to improve the skills of applied science and technologybeing transferred to the public; (4) Assistance is ongoing meetings between the chaperone with the targetcommunities so that science and technology are transferred can be carried out independently by thecommunity. The results obtained show that the dissemination of science and technology activities for theregions in Batubulan village, sub-district Sukawati, Gianyar can take place properly, the active participationof society and the adoption of science and technology is high. Active participation of partners in all activitiesof technology dissemination is high at 68%. Adoption of science and technology capabilities and partners'initiatives to produce seeds independently is quite high at 50%.